Optimization in Industry Present Practices and Future Scopes - Datta, Shubhabrata; Davim, J. Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book describes different approaches for solving industrial problems like product design, process optimization, quality enhancement, productivity improvement and cost minimization. Several optimization techniques are described. The book covers case studies on the applications of classical as well as evolutionary and swarm optimization tools for solving industrial issues. The content is very helpful for industry personnel, particularly engineers from the Operation, R&D and Quality Assurance sectors, and also the academic researchers of different engineering and/or business administration background.
Optimization for Industrial Problem Solving: an Introduction -- Operational Research and Optimization.-Traditional Optimization Techniques -- Evolutionary algorithms -- Swarm Optimization -- Multi-objective Optimization and Multi-criteria Decision Making -- Product Design and Optimization -- Process Optimization and Control -- Optimization in Manufacturing Sector -- Optimization in Chemical Industries -- Optimization in Construction and Transport Engineering -- Optimization in Electronic and Communication Sector -- Optimization in Steel Industries -- Optimization in Supply Chain and Logistics. .
Keywords: Industrial engineering; Production engineering; Production management; Chemistry, Technical; Industrial and Production Engineering; Operations Management; Industrial Chemistry